(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
The paper analyzes the proposal to amend the core element of the Common European Asylum System, Dublin IV Regulation, from two different perspectives – principle of solidarity between Member States and protection of asylum seekers’ human rights. An in-depth analysis is provided of novel solutions introduced by Dublin IV, their comparison with provisions contained in Dublin III, as well as an intersection of current state of negotiations between Member States within relevant EU institutions with a view to reach an acceptable version of the future document. The focus is on two important issues. Firstly, does Dublin IV enhance solidarity between Member States or does it do the exact opposite – further regresses the poor level of solidarity attained in Dublin III? Solidarity principle is implemented through a number of Dublin IV provisions, such as those concerning equitable distribution of applicants for international protection, the new fairness mechanisms and corrective allocation mechanisms. However, it remains to be seen whether these and other mechanisms based on solidarity principle will have any meaningful effect and whether there are any realistic prospects of applying them in practice, especially taking into account rather negative previous experiences. Secondly, changes brought by Dublin IV are analyzed from the perspective of human rights protection. This part of the paper focuses on certain problematic issues that emerge with regard to the level of human rights protection guaranteed by the Regulation and its compatibility with relevant standards established in the case-law of both the Court of Justice of the European Union and the European Court of Human Rights. Namely, application of a number of provisions contained in Dublin IV may easily result in violations of asylum seekers’ human rights, right to family life and prohibition of torture in particular. This may seriously weaken the protection of fundamental rights of asylum seekers, especially rights of vulnerable asylum seekers, attained through the jurisprudence of two European courts. In the two enumerated operative parts of the paper attempts are made to assess the position of Dublin IV changes as compared not only to its currently applicable counterpart, but also to common European standards born out of application of Dublin system in practice, from the perspectives of both the principle of solidarity and human rights protection. It appears that the proposed Dublin IV Regulation tends to sacrifice protection of human rights for the sake of the principle of solidarity. Since attainment of solidarity in practice is not warranted, the proposed regulation may end up making both the principle of solidarity and protection of human rights illusions rather than imperatives, making way for a preferred but highly debatable aim of a more functional asylum system.